MEMAHAMI DRAMA JAKA TARUB KARYA AKHUDIAT - Roesmiati, Dian (ATAVISME, 2007)
Drama is one of literature genres that shows significant progress. This paper is driven by the lack of drama scripts, particularly those of local scriptwriters who brought about local distinctiveness. Jaka Tarub is one of Akhudiat's works which won the drama script writing contest in Dewan Kesenian Jakarta (DKJ) in 1974. The aims of this paper are to discover Akhudiat's profile as a writer, along with his creative process, as well as the structure of Jaka Tarub as a drama. The drama of Jaka Tarub is interesting to study because the plot is unique and the central figures are deconstructed, thus it is no longer the same as that of before. As a writer, Akhudiat has given today's style and taste into the drama.